MOBILE APPLICATION FOR UNIMAS SPORT COMPLEX - POY, VENLY (Universiti Malaysia Sarawak(UNIMAS), 2018)
Sport complex is a place where suits for playing sports, having activities and organising events. Meanwhile, UNIMAS Sport Complex also provides variety of services for student, staff and guest. This research will produce a mobile application for the target audience. With this application, it bring convenient to users to manage booking in the fastest way.